Cover Picture: Lamellar versus Micellar Structures—Aggregation Behavior of a Three‐Chain Cationic Lipid Designed for Nonviral Polynucleotide Transfer (ChemPhysChem 10/2015). Issue 10 (20th July 2015) - Wölk, Christian; Janich, Christopher; Pawlowska, Dorota; Drescher, Simon; Meister, Annette; Hause, Gerd; Dobner, Bodo; Langner, Andreas; Brezesinski, Gerald
<x xml:space="preserve">Abstract</x> DiTT4, a three‐chain amino‐functionalized lipid designed for gene transfer, exhibits unusual aggregation behavior; it forms bilayer structures at pH 10 and 7.3, and rod‐like micelles at pH 5. The thermotropic and lyotropic behavior is studied using differential scanning calorimetry, small‐angle X‐ray scattering, and FTIR spectroscopy, as reported by C. Wölk et al. on p 2115. Complementary dynamic light scattering experiments and transmission electron microscopy (TEM and cryoTEM) are also used. In addition, investigations at the air–water interface are performed by recording area‐pressure‐isotherms and infrared reflection‐absorption (IRRA) spectra. The ability of DiTT4 to complex plasmid DNA is investigated using fluorescence techniques and zeta potential measurements.